Change in the prevalence of overweight/obesity in Czech seven-year-old children between 2008 and 2019 - Metelcová, Tereza; Zamrazilová, Hana; Procházka, Bohuslav; Braunerová, Radka Taxová; Kunešová, Marie (Casopis lekaru ceskych, 2023)
World Health Organization (WHO) Europe organizes Childhood Obesity Surveillance Initiative (COSI), in which the Czech Republic participates since the beginning. The aim of this project is to monitor the prevalence of overweight and obesity of 7-year-old children in the Czech Republic. Data were obtained from 2349 children examined by 72 pediatricians across the Czech Republic. Anthropometric parameters were measured and subjects filled questionnaire. The prevalence of obesity and overweight did not change significantly between 2008 and 2019. Although in the fifth round in 2019, the prevalence of obesity increased and the prevalence of overweight slightly decreased in both sexes. In 2019 6.09 % of boys and 7.12 % of girl had overweight. The prevalence of obesity in the fifth round was 9.26 % in boys and 8.64 % in girls (assessed according to the Czech reference values). Already in the first round we noticed a relatively high prevalence of severe obesity (3.21 % for boys and 0.8 % for girls), which did not differ significantly between rounds. Even if the prevalence of overweight has not significantly increased until 2019, preventive and treatment programs are very important, because it is an important part of the prevention and early detection of obesity in children.
Keywords: severe obesity; Humans; index tělesné hmotnosti; Body Mass Index; Overweight; dítě; prevalence; Child; Pediatric Obesity; Female; overweight; children; lidé; body mass index; COSI; ženské pohlaví; obezita dětí a dospívajících; Male; Czech Republic; Prevalence; Česká republika; mužské pohlaví; obesity; nadváha